Holy Week and Easter 1931 - Patrick, William E.; St. Paul’s Episcopal Church (Bakersfield, Calif.)
Service program for Holy Week and EasterFolded announcement for Holy Week services held in 1931 at St. Paul's Episcopal Church. Includes letter to parish from rector Reverend Patrick.